TERAPI FORGIVENESS UNTUK MENINGKATKAN SELF ESTEEM PADA REMAJA KORBAN PERSELINGKUHAN DALAM HUBUNGAN BERPACARAN - Zuroida, Aironi; Kireida Kusnadi, Starry; Milenia Putri, Futy Oktav (IDEA: Jurnal Psikologi, 2024)
Teenagers are individuals who are in puberty, during this period teenagers begin to feel attracted to the opposite sex and start dating. In a dating relationship it doesn't always run smoothly, one of the problems in a dating relationship is infidelity. The phenomenon of infidelity in teenagers results in teenagers having a negative self-evaluation, this happens because individuals who have been cheated on tend to feel rejected, have difficulty seeing themselves as valuable and need other people's opinions to accept themselves so that self-esteem decreases. One way to get rid of negative feelings is with forgiveness therapy. This research aims to determine the effectiveness of forgiveness therapy to increase the self-esteem of adolescent victims of infidelity. This research uses a quasi-experimental research design and uses a one group posttest-pretest technique with purposive sampling of subjects, namely teenagers aged 12-21 years who have had the experience of being cheated on and have not been able to forgive. Statistical tests were analyzed using Paired Sample T-Test. The results show a 2-tailed sig value of 0.004 < 0.005, which means that it is significant, giving Forgiveness Therapy is effective in increasing the self-esteem of Adolescent Victims of Infidelity so that they can be forgiving and able to minimize the tendency of decreasing self-esteem.